The Great War in Poland-Lithuania from A Jewish Perspective: Modernization and Orientalization - Martin Ernst Rudolf Arndt (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
The article presents views of Eastern Judaism, especially in Lithuania, in the Jewish press around the Great War. It is based on a close research of journals, newspapers and book-publications written in the German language. It evidences the global implications of the Great War due, among others, to forced and voluntary migrations that involved cultural encounters, confrontations and challenges. The Other, signifying a collective excluded from the social whole, in those days perceived in the Eastern Jew, meant an embarrassment to the Western Jews (Albanis: 30) and served the function of constructing self-identity, involving them in conflicts or making them develop a dual allegiance (Moshe Gresser; Albanis). Should Jews, if they were to become proper Europeans, not decisively shed their Asian being and carriage and thus de-orientalize themselves? The paper also demonstrates that this historical phase of Jewish history, as it deeply involves the problem of secularization, is connected to intricate problems of identity. It can also illustrate a certain openness and fluidity of identitarian possibilities. The issues involved have a clear relevance for contemporary societies, centred around the question if modernity requires minorities to surrender their particularism, or if is there a suble dialectic between universalism and particularism. Implicitly the core issue also raises the question of a common history of Islam and Judaism and the current problem if antisemitism, as targeted at the Eastern Jews, is comparable to contemporary Islamophobia.